Wing morphological responses to latitude and colonisation in a range expanding butterfly - Taylor-Cox,Evelyn D.; Macgregor,Callum J.; Corthine,Amy; Hill,Jane K.; Hodgson,Jenny A.; Saccheri,Ilik J. (PeerJ, 2020)
Populations undergoing rapid climate-driven range expansion experience distinct selection regimes dominated both by increased dispersal at the leading edges and steep environmental gradients. Characterisation of traits associated with such expansions provides insight into the selection pressures and evolutionary constraints that shape demographic and evolutionary responses. Here we investigate patterns in three components of wing morphology (size, shape, colour) often linked to dispersal ability and thermoregulation, along latitudinal gradients of range expansion in the Speckled Wood butterfly (Pararge aegeria) in Britain (two regions of expansion in England and Scotland). We measured 774 males from 54 sites spanning 799 km with a 10-year mean average temperature gradient of 4 °C. A geometric morphometric method was used to investigate variation in size and shape of forewings and hindwings; colour, pattern, and contrast of the wings were examined using a measure of lightness (inverse degree of melanism). Overall, wing size increased with latitude by ∼2% per 100 km, consistent with Bergmann’s rule. Forewings became more rounded and hindwings more elongated with history of colonisation, possibly reflecting selection for increased dispersal ability. Contrary to thermal melanism expectations, wing colour was lighter where larvae developed at cooler temperatures and unrelated to long-term temperature. Changes in wing spot pattern were also detected. High heterogeneity in variance among sites for all of the traits studied may reflect evolutionary time-lags and genetic drift due to colonisation of new habitats. Our study suggests that temperature-sensitive plastic responses for size and colour interact with selection for dispersal traits (wing size and shape). Whilst the plastic and evolutionary responses may in some cases act antagonistically, the rapid expansion of P. aegeria implies an overall reinforcing effect between these two mechanisms.
Keywords: Range expansion; Geometric morphometrics; Dispersal; Laitude; Temperature-size rule; Bergmann’s rule; Thermal melanism; Lepidoptera; Pararge aegeria; Wings